Concurrence of plants and its representation in Indonesian proverbs - Wijana, I Dewa Putu (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This brief article deals with the concurrence of plants or its parts and its representations in Indonesian proverbs. The data used are mostly extracted from Indonesian proverb books, and ones found in proverbs of other languages. First, the data are classified based on plants or parts of plant possibly concurred. Later, the investigation is directed toward the various possibility the combination might represent. Through careful analysis, it is finally found that the plants or parts of the plants to be combined can be between different plants, parts of the same plants, one plant and its parts, parts and different plants, and parts of different plants. Plants or parts of plants to be combined are perceived as: to have the same quality for representing something hard or impossible to change, something must be committed by both parties, the same destiny to be experienced, or how should someone to behave; the different quality of plants or parts of the plant is used to represent unexpected thing (better or worse) to happen, not easy to give up and always depend on something available, could differentiate between good and bad matters, to use the worse quality things first before the better ones, imbalance competition, ability and sincerity to accept the good and bad aspect of things; one plant or parts of the plant are older (coming out earlier) or younger (coming out later) than the others to represent the difficulties for the older people to change, any occasion follows cause and effect law, the new comers usually should or could not drive out or defeat the natives; and phonological representation to show that sometimes the proverbs are created on the basis of aesthetic achievements instead of merely on metaphorical similarities.